Create e-books using HTML and CSS (Texas Journal of Multidisciplinary Studies, 2023)
This Research paper is talking about the various valuable coding languages and software, methods that are utilized in the process of advancement of a website. The main Purpose Of this project is to create a Self-Designed Website using HTML, CSS, and JS, which is not only Unique, but it is highly Optimized also, and make sure that this Website is used for Online Business such as Shopping, Blogging, DigitalMarketing, etc. We will attempt to utilize the WordPress for nearby hosting of the site. Through WordPress viewpoint can see effectively by the engineer and client and change the code according to necessity. WordPress is a free opensource cross stage created by Apache and comprising HTTP worker and deciphers with the contents written in HTML-CSS & JS programming language. It is basic, adaptable and light weight device that can makes extremely simple for designers to make a nearby web worker for site testing what's more, advancement measure. The scope and essentialness work are given here under. In existing work, no worker space is utilized and no expense utilization for DNS will be utilized. Applying the PHP Coding with help and certainty detail on various phases of plans will improve the precision. Client will ready to determine all the clearer perception with respect to of site, effectively can include content. We also create 3-4 websites which can be used to Blogging, Marketing, Advertising, etc. Our development process enables the rendering of Web pages in a very fast and optimized way by ensuring the good user experience on mobile, tablet and desktop devices